2018
DOI: 10.1111/sltb.12535
|View full text |Cite
|
Sign up to set email alerts
|

Help‐seeking Behavior in Socially Conservative and Christian Suicide Decedents

Abstract: Objective The purpose of this study was to examine the relationship between religious affiliation, political beliefs, and lifetime mental health help‐seeking behavior in a sample of suicide decedents. We hypothesized that Christian decedents would be less likely to have sought help than non‐Christians, and socially conservative individuals would be less likely to have sought help than socially liberal or moderate individuals. Method Smaller samples (N = 147 for political analyses, N = 218 for religion analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Most studies were adequate on Items 1 and 2, while close to half of studies were rated as partial for item 3 and poor for item 4. Only eight studies scored less than adequate on >50% of the items ( 31 , 36 , 53 , 54 , 56 , 68 , 73 , 76 ). Excluding these studies did not meaningfully alter the results.…”
Section: Resultsmentioning
confidence: 95%
“…Most studies were adequate on Items 1 and 2, while close to half of studies were rated as partial for item 3 and poor for item 4. Only eight studies scored less than adequate on >50% of the items ( 31 , 36 , 53 , 54 , 56 , 68 , 73 , 76 ). Excluding these studies did not meaningfully alter the results.…”
Section: Resultsmentioning
confidence: 95%
“…Six studies focused on suicide decedents and retrospectively examined their service use prior to suicide. Specifically, 4 articles reported on suicide decedents’ service use up to 1 year prior to suicide ( 43–46 ), 1 study reported on service use during the last 2 years of the decedents’ life ( 47 ), and another examined loss survivors’ knowledge of whether and when decedents sought help for mental health concerns at some point during lifetime and prior to death ( 48 ). Most of the articles ( n = 5) in this category reported quantitative analysis results ( 43 , 44 , 46–48 ); 1 study reported mixed-methods findings ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies reported that the majority of suicide decedents sought help in their last years of life. The prevalence of service contact or utilization ranged from 75% ( 48 ) to 87% ( 44 ). A range of service contact and/or utilization were examined and reported in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations